A Multigroup Invariance Analysis and Gender Difference of Students Self-efficacy and Attitude Concerning Mathematics - Elizar Elizar; I Gusti Ngurah Darmawan (Universitas Syiah Kuala, 2018)
This article aimed to examine multigroup invariance of Mathematics Self-efficacy and Attitude Scales (MSAS) and examine the differences of MSAS in term of gender. 1135 (630 female and 505 male) Year 9 students in Aceh, Indonesia were involved in the study. The invariance analysis was performed to investigate whether the items in the MSAS are behaving identically for Year 9 female and male students in the province of Aceh, Indonesia. The results reported the indication of multigroup equivalence of the MSAS between gender (p-value is not statistically significant orCFI0.01). An independent t-test indentified that students attitude concerning mathematics is significantly different between gender of students. Female students positive attitude concerning mathematics is higher compared to male students. This study may be used as one of the evidences as for the needs to enhance male students attitude toward mathematics.